Breastfeeding and vitamin D supplementation reduce the risk of Kawasaki disease in a German population-based case-control study - K. Meyer; A. Volkmann; M. Hufnagel; E. Schachinger; S. Klau; J. Horstmann; R. Berner; M. Fischer; A. Lehner; N. Haas; S. Ulrich; A. Jakob (BMC, 2019)
Abstract Background In Kawasaki disease (KD), a vasculitis of unknown etiology, the most serious complication is the development of coronary artery aneurysm (CAA). To date, the exact pathomechanism of KD is unknown. Both environmental and genetic factors seem to be associated with the development of the disease. Methods Data on KD patients recruited from the population-based German Pediatric Surveillance Study during 2012-2014 were used to evaluate the impact of various factors from the perinatal and infancy period on the development of KD. The study design was a matched case-control study with respect to age, sex and place of residence (n = 308 KD cases, n = 326 controls). All KD patients were individually re-evaluated; all fulfilled the international diagnostic KD criteria. A standardized questionnaire was used to review breastfeeding practices, vitamin D supplementation and birth characteristics. Logistic regression analyses were performed to obtain odds ratios (OR) for various risk factors among the case-control pairs. Simple measures of association were used to assess the impact of these factors on the clinical course. Results There was no difference in lengths of gestation, birth weight or parturition between KD patients and controls, but independently from each other vitamin D supplementation and breastfeeding were negatively associated with KD, even when adjusted for age, place of residence and sex. The duration of vitamin D was significantly shorter among children with KD than among children without KD (p = 0.039, OR = 0.964, 95% CI: 0.931-0.998), as was the duration of breastfeeding (p = 0.013, OR = 0.471, 95% CI: 0.260-0.853). Comparing KD patients with and without breastfeeding and/or vitamin D supplementation, there were no differences regarding developing CAA, being refractory to intravenous immunoglobulin treatment, age at onset of the disease and levels of inflammatory laboratory values. Conclusion Our findings indicate breastfeeding and vitamin D supplementation to have protective effects in association with KD in our study population; however, these seem not to influence the natural course of the disease. Although the overall effects were relatively small, they nevertheless underline the overall benefit of both interventions. Trial registration Clinical Trial Registration: German clinical trial registration, http://apps.who.int/trialsearch/Trial2.aspx?TrialID=DRKS00010071. Date of registration was 26. February 2016. The trial was registered retrospectively.